Identification of SARS-CoV-2 inhibitors from alkaloids using molecular modeling and in silico approaches - Roni, Md Abul Hasan; Mortuza, Md. Golam; Rozina, .; Shaha, Ripon Kumar; Hoque, Sajidul; Kumer, Ajoy (Sami Publishing Company, 2023)
Having a wide range of pharmacological action antiviral properties of alkaloids, these were focused on this study for computational screening against SARS-CoV-2 proteases. However, 256 alkaloids from PubChem databased, 10 compounds were selected by PASS prediction for primally observation having active value against virus with the main protease (Mpro) of acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Besides, the pharmacokinetics and Lipinski's rule of five (RO5) were evaluated for all molecules being drug likeness properties, and then these were selected for molecular docking against the Mpro of corona virus, and L-03, L-07, and L-13 found the best-bonded molecules accounting weak H bonding and hydrophobic bond interactions. In addition, on the binding energies of Mpro, L-3, L-7, L-13, L-18, L-25, L-26, L-34, L-39, L-42, and L-49 were at -8.6, -8.3, 8.2, -8.1, -8.0, -7.9, -7.9, -7.9, and -7.9 kcal/mol. Overall, L-3 is considerable best candidate with Mpro in view of the molecular docking score. In addition, the quantum properties, chemical hardness and softness values were calculated. Finally, from admetSAR online database, absorption, distribution, metabolism, excretion, and toxicity (ADMET) were evaluated. Lastly, L-3, L7, and L-13 were satisfied the toxicity category. In comparison to the World Health Organization (WHO) guidelines, FDA-approved antiviral drugs, favipiravir and remdesivir, which have binding energies of -5.1 and -8.1 kcal/mol of the Mpro, respectively. In this case, our selected L-3, L-7, L-13, and L-18 have binding energies of -8.6, -8.3, -8.2, and -8.2 kcal/mol, respectively. Thus, the L-3, L-7, L-13 and L-18 molecules will have strong activity against the SARS-CoV-2.